Content validity of an instrument for assessing skin lesions in a mother and child hospital - Aguirre, Victória Campos de Souza Plasencia; Dória, João Pedro da Silva; Melo, Rosana Alves de; Fernandes, Flávia Emília Cavalcante Valença; Mola, Rachel (Revista de Enfermagem da UFPI, 2024)
Objective: To describe the process of validating an instrument for assessing skin lesions in a maternal and child hospital. Methods: A methodological study of evidence of content validity was carried out between May and July 2022 in a mother and child service. The selection criteria for the experts were: being a nurse working in research or assisting patients with skin lesions. The instrument was sent by email via Google® forms, containing 23 items grouped into five topics on patient identification and hospitalization data, location and characterization of the lesions, and nursing care provided. The items were judged in terms of agreement using the Likert scale; qualitative evaluation of the instrument was also allowed, by including suggestions for the items presented. Results: Validation was carried out by 22 nurses using the Delphi technique, followed by reliability tests. All the items assessed obtained a level of agreement above 80%. Based on the score for each item, new tests were carried out to assess agreement with the instrument as a whole, resulting in the validation of its final version. Conclusion: The methodological validation process applied showed a high level of agreement, representing a cohesive instrument in the theoretical a...